The relationship between rock climbing and total body strength and endurance - Gamma, M.; Bruce, A.; Massey, M.; Cordero, A. (The Corinthian, 2019)
Rock climbing is a physically and mentally demanding sport and is growing in popularity of its recreational form. There are various types of rock climbing including bouldering, free climbing, top rope climbing, and alpine climbing to name a few. However, the most popular subdivision of rock climbing to date is indoor top rope climbing (Draper, Jones, Fryer, Hodgson, & Blackwell, 2014). Top rope climbing involves the climber being harnessed and connected to a rope that runs from the climber`s harness to a pulley-clip located at the top of the wall then through the harness of the belayer, who remains at ground level. This type of climbing decreases the risk of injury to the climber since the belayer has more control over the fall distance. Top rope climbing is tailored to novice and experienced climbers alike and, when conducted indoors, it allows participants to climb at any time, regardless of outdoor conditions. There are many factors that can influence a person`s ability to climb, including both psychological and physical factors. Rock climbing ability can be influenced by body mass as well as upper and lower body strength and endurance. Most climbers have a high strength to mass ratio with a smaller physique which allows them to climb more efficiently (Giles, Rhodes, & Taunton, 2006). A smaller body mass can give climbers a climbing advantage because body mass is the main resistive force on the body during a climb (Ozimek, Staszkiewicz, Rokowski, & Stanula, 2016). Previous research has identified an association between upper body strength and endurance and improvements in climbing performances. The movements performed during rock climbing provide a large amount of force to the upper body. While climbing, there are instances where the hands and fingers are supporting total body weight (Stankovic, Joksimovic, & Aleksandrovic, 2011). Total body support is necessary for rock wall climbing because the lower body provides the strength Volume 19 | Spring 2019 to propel the individual through the course, whereas, the upper body will provide the strength to move in different directions throughout the climb. Past studies have used various strength and endurance tests to assess muscular strength and endurance, such as grip strength, finger strength, and flexed arm hang tests (Grant, Hasler, Davies, Aitchison, Wilson, & Whittaker, 2001). Grip strength and finger strength have been used in multiple studies as predictors of an individual`s climbing performance. Gurer and Yildiz (2015) claim that insufficient grip strength "is generally one of the main reasons for [failing] a climb route." It has been shown that the right hand has a greater handgrip strength when compared to the left hand, and therefore may play a more dominate role in the climbing process (Gurer, & Yildiz, 2015). While upper body strength and endurance can indicate performance, the lower body also plays a vital role in climbing ability. During a vertical rock wall climb, more of the body mass is supported by the legs (Watts et al., 2008). This especially pertains when the body is driven upward during a climb because the lower limbs do not fatigue as quickly as their upper counterparts (Michailov, 2014). Lower body strength and endurance are frequently tested using leg press exercises (Escamilla et al., 2001). The leg press is a common multi-joint exercise utilized to enhance performance in sports, as it recruits large and powerful muscles. Rock climbing performance requires efforts of the entire body, so assessing strength and endurance of the lower body may provide another indicator for climbing performance. Past research has assessed the impact that muscular strength and endurance can have on climbing ability for elite and trained climbers. There remains a need for further research on the impact that muscular strength and endurance has on the general population. Rock wall climbing has become a recent trend for all ages and experience levels. Identifying the importance of upper and lower body strength and endurance can potentially set interested participants at ease by showing them that they do not have to have years of experience to excel at climbing. Instead, simply practicing rock climbing has been shown to be an effective technique for improving performance (Furlonger, 2017). Previous research has found that successful climbing i related to total body muscular strength and endurance, so individuals of all skill levels should have a faster climb if they already possess those traits. The purpose of our study was to assess whether muscular The Corinthian | The Journal of Student Research at Georgia College strength and endurance ability can lead to a faster rock wall climb. Therefore, we hypothesized that if an individual performs better on their muscular strength and endurance tests, then they will have a shorter time to completion for their climb.